Effect of environmental and phenological factors on the antimicrobial activity of Cochlospermum regium (Schrank) Pilg. roots - Inacio, Marielle Cascaes [UNESP]; Paz, Tiago Antunes [UNESP]; Bertoni, Bianca Waleria; Soares Pereira, Ana Maria (Univ Estadual Maringa, Pro-reitoria Pesquisa Pos-graduacao, 2016)
Cochlospermum regium (Bixaceae) is a medicinal plant species native to the Brazilian savannah, known as the Cerrado. Local communities use its roots to treat infections of the female reproductive system. This study evaluated how seasonality, phenological stage, geographical location, plant age, and plant cultivation substrate affect the antimicrobial activity of Cochlospermum regium roots against Candida albicans. Although the plant displayed antimicrobial action in all the assayed conditions, the roots collected during fall and winter inhibited C. albicans the most effectively. The geographical location in which the plant material was found did not influence its biological response. Plant age and cultivation substrate did impact the biological response; those grown in sand showed fungicidal activity, while those grown in Cerrado soil fertilized with cow dung showed fungistatic activity during certain periods. The inner bark and core of the root were the main structures underlying the antimicrobial activity of Cochlospermum regium.
Keywords: Bixaceae; STAMP (Screening Test for Antibiotics in Medicinal Plants); Candida albicans; Cerrado; algodaozinho-do-campo